2021
DOI: 10.1155/2021/1809005
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Coordination between Technology Transfer in Universities and High‐Tech Industries Development in China

Abstract: Only through successful transformation and application in industries, technology achievements in universities can promote economic and social development. Meanwhile, technological progress in high-tech industries depends in part on universities’ technology achievements. Coupling coordination between technology transfer in universities (TTU) and high-tech industries development (HTID) is of great significance to the sustainable development of the regional sci-tech innovation system. In this paper, the coupling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 69 publications
(65 reference statements)
0
12
0
Order By: Relevance
“…The steps for screening indicators and determining weights include (1) calculating the eigenvalues of the index correlation coefficient matrix, (2) determining the key factors to be retained, (3) calculating the factor loading matrix, (4) calculating the information contribution rate of the indices, (5) calculating the cumulative information contribution rate, (6) screening indicators with a high information contribution rate, (7) checking the necessity of eliminating information overlap indicators, (8) eliminating indicators with a high degree of information overlap, and (9) determining the weight of the evaluation indices. The detailed calculation process can be found in the related reference [ 56 ], and the results are shown in Table 1 . To reflect the comparability of data between provinces, all indices are used per capita data.…”
Section: Methodology and Data Sourcesmentioning
confidence: 99%
“…The steps for screening indicators and determining weights include (1) calculating the eigenvalues of the index correlation coefficient matrix, (2) determining the key factors to be retained, (3) calculating the factor loading matrix, (4) calculating the information contribution rate of the indices, (5) calculating the cumulative information contribution rate, (6) screening indicators with a high information contribution rate, (7) checking the necessity of eliminating information overlap indicators, (8) eliminating indicators with a high degree of information overlap, and (9) determining the weight of the evaluation indices. The detailed calculation process can be found in the related reference [ 56 ], and the results are shown in Table 1 . To reflect the comparability of data between provinces, all indices are used per capita data.…”
Section: Methodology and Data Sourcesmentioning
confidence: 99%
“…Within the framework of research reported in [3], it was concluded that the technology, as a result of its transfer, has a significant impact not only on economic relations but also on the environment. Under such conditions, the prevailing means of determining the safety of technology through intellectual property mechanisms are not effective.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…All the studies analyzed above [1][2][3][4][5][6][7][8] testify to the focus of scientific research on solving the issue of limiting the freedom to use technology, taking into account the interests of public safety. No works were found within which generalized constructions of regulatory techniques were formed.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…In China, there is significant regional heterogeneity in sci-tech collaborative efficiency, and human capital and financing are important channels for promoting the integration of technology and finance [ 43 ]. Additionally, the development of science and technology finance has a positive impact on the coupling coordination between the technology transfer of universities and high-tech industries [ 44 ].…”
Section: Literature Reviewmentioning
confidence: 99%